Global Tourism Transformation: A Review of Destination Marketing Innovations and Strategies - Sukand, Gayatri (Journal of Global Tourism, 2024)
The transformation of global tourism has driven various innovations and marketing strategies to face the increasingly fierce competition in the digital era. With the emergence of new technologies such as augmented reality (AR), virtual reality (VR), and big data, tourist destinations are able to provide more personal and immersive experiences for tourists. This study aims to explore technological innovations and effective marketing strategies in increasing the attractiveness and sustainability of tourist destinations. Using a literature study method, this study analyzes various scientific articles from reputable databases that discuss the application of technology, experiential marketing strategies, and sustainability approaches in the tourism industry. The results show that the application of VR and AR technology can increase tourist engagement, while experiential and sustainability marketing strategies increase loyalty and destination image. In addition, big data allows for effective personalization of marketing content, while sustainability approaches attract environmentally conscious tourists. This study concludes that the integration of digital technology and experiential marketing and sustainability can strengthen the competitiveness of tourist destinations in the global market. These findings provide practical guidance for tourism managers in developing innovative, sustainable, and adaptive strategies to changing trends.